Redox-Active Sensing by Bacterial DksA Transcription Factors Is Determined by Cysteine and Zinc Content - Matthew A. Crawford (American Society for Microbiology, 2016)
ABSTRACT The four-cysteine zinc finger motif of the bacterial RNA polymerase regulator DksA is essential for protein structure, canonical control of the stringent response to nutritional limitation, and thiol-based sensing of oxidative and nitrosative stress. This interdependent relationship has limited our understanding of DksA-mediated functions in bacterial pathogenesis. Here, we have addressed this challenge by complementing ΔdksA Salmonella with Pseudomonas aeruginosa dksA paralogues that encode proteins differing in cysteine and zinc content. We find that four-cysteine, zinc-bound (C4) and two-cysteine, zinc-free (C2) DksA proteins are able to mediate appropriate stringent control in Salmonella and that thiol-based sensing of reactive species is conserved among C2 and C4 orthologues. However, variations in cysteine and zinc content determine the threshold at which individual DksA proteins sense and respond to reactive species. In particular, zinc acts as an antioxidant, dampening cysteine reactivity and raising the threshold of posttranslational thiol modification with reactive species. Consequently, C2 DksA triggers transcriptional responses in Salmonella at levels of oxidative or nitrosative stress normally tolerated by Salmonella expressing C4 orthologues. Inappropriate transcriptional regulation by C2 DksA increases the susceptibility of Salmonella to the antimicrobial effects of hydrogen peroxide and nitric oxide, and attenuates virulence in macrophages and mice. Our findings suggest that the redox-active sensory function of DksA proteins is finely tuned to optimize bacterial fitness according to the levels of oxidative and nitrosative stress encountered by bacterial species in their natural and host environments. IMPORTANCE In order to cause disease, pathogenic bacteria must rapidly sense and respond to antimicrobial pressures encountered within the host. Prominent among these stresses, and of particular relevance to intracellular pathogens such as Salmonella, are nutritional restriction and the enzymatic generation of reactive oxygen and nitrogen species. The conserved transcriptional regulator DksA controls adaptive responses to nutritional limitation, as well as to oxidative and nitrosative stress. Here, we demonstrate that each of these functions contributes to bacterial pathogenesis. Our observations highlight the importance of metabolic adaptation in bacterial pathogenesis and show the mechanism by which DksA orthologues are optimized to sense the levels of oxidative and nitrosative stress encountered in their natural habitats. An improved understanding of the conserved processes used by bacteria to sense, respond to, and limit host defense will inform the development of novel strategies to treat infections caused by pathogenic, potentially multidrug-resistant bacteria.